Chyloptysis with Right Middle Lobe Syndrome Complicated Postoperatively by Chylothorax: An Unusual Cause of Right Middle Lobe Syndrome - Chamani Illamperuma; John Reid; Rani Kanthan (Canadian Respiratory Journal)
Chyloptysis, in the context of middle lobe syndrome, and chylothorax are rare clinical entities. They are reported in the medical literature mostly as case reports, but never together in the same patient. The present report describes the case of a 34-year-old woman who presented with chyloptysis associated with recurrent right middle lobe syndrome since she was 20 years of age, and eventually underwent right middle lobectomy. A few weeks postoperatively, she developed a right-sided chylothorax, which was refractory to medical therapy, and was successfully treated with thoracic duct ligation. She has been symptom-free for two years postsurgery.